Pengaruh Literasi Keuangan, Persepsi Resiko, dan Media Sosial Terhadap Minat Investasi Saham (Studi Kasus Pada Wanita Generasi Z di Kota Malang) - Moh Firman Ariansyah; Mohamad Bastomi; Dita Roosemella Paramadina (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the influence of financial literacy, risk perception, and social media on stock investment interest. This research employs an explanatory research design using a quantitative method. The population of this study consists of Generation Z women in Malang City, with a sample of 102 respondents selected using purposive sampling. Primary data were collected through questionnaires, and SPSS version 26.0 was used as the data analysis tool. The results show that simultaneously, financial literacy, risk perception, and social media have a significant effect on stock investment interest. Partially, financial literacy and social media have a positive and significant effect on stock investment interest, while risk perception does not have a significant effect. These findings indicate that stock investment interest among Generation Z women is more influenced by financial understanding and the use of social media as a source of investment information than by perceptions of investment risk. Keywords : Financial Literacy, Risk Perception, Social Media, Stock Investment Interest, Generation Z